2015
DOI: 10.1016/j.jconrel.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression kinetics of nucleoside-modified mRNA delivered in lipid nanoparticles to mice by various routes

Abstract: In recent years, in vitro transcribed messenger RNA (mRNA) has emerged as a potential therapeutic platform. To fulfill its promise, effective delivery of mRNA to specific cell types and tissues needs to be achieved. Lipid nanoparticles (LNPs) are efficient carriers for short-interfering RNAs and have entered clinical trials. However, little is known about the potential of LNPs to deliver mRNA. Here, we generated mRNA-LNPs by incorporating HPLC purified, 1-methylpseudouridine-containing mRNA comprising codon-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
709
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 767 publications
(743 citation statements)
references
References 27 publications
29
709
0
5
Order By: Relevance
“…For example in the study by Zangi et al, protein expression driven by exogenously administered mRNA returned to baseline within 48–72 hours post-injection [3]. Similar findings were reported with intravenously administered mRNA [4]. Unlike small RNAs, such as siRNA, that can be synthesized to have extended half-lives, in vitro transcribed mRNA is not as amenable to stability conferring chemical modifications.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For example in the study by Zangi et al, protein expression driven by exogenously administered mRNA returned to baseline within 48–72 hours post-injection [3]. Similar findings were reported with intravenously administered mRNA [4]. Unlike small RNAs, such as siRNA, that can be synthesized to have extended half-lives, in vitro transcribed mRNA is not as amenable to stability conferring chemical modifications.…”
Section: Introductionmentioning
confidence: 61%
“…For example, Zangi et al used intra-myocardial injection of exogenous luciferase or VEGF-A mRNA to increase local protein production in the heart and improved survival in a preclinical myocardial infarction model [3]. Moreover, lipid nanoparticle formulated mRNA has been successfully delivered to the liver, spleen and lung in preclinical models [46]. One major drawback of mRNA based therapy is the relatively short half-life of exogenously delivered mRNA in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering of the RNA sequence has rendered synthetic mRNA more translatable than ever before. Highly efficient and non-toxic RNA carriers have been developed that in some cases 21,22 allow prolonged antigen expression in vivo (TABLE 1). Some vaccine formulations contain novel adjuvants, while others elicit potent responses in the absence of known adjuvants.…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
“…81), but it has only recently been shown that LNPs are potent tools for in vivo delivery of self-amplifying RNA 19 and conventional, non-replicating mRNA 21 . Systemically delivered mRNA–LNP complexes mainly target the liver owing to binding of apolipoprotein E and subsequent receptor-mediated uptake by hepatocytes 82 , and intradermal, intramuscular and subcutaneous administration have been shown to produce prolonged protein expression at the site of the injection 21,22 . The mechanisms of mRNA escape into the cytoplasm are incompletely understood, not only for artificial liposomes but also for naturally occurring exosomes 83 .…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
“…On the other hand, the synthetic mRNA utilized in this study contains pseudouridine-and 5-methylcytidinesubstituted nucleotides along with a poly A tail at the 3′ end (120 adenosine residues) for optimal mRNA expression, which has been demonstrated in previous studies. [1][2]20] Since each PABP protein is known to bind a continuous stretch of 12 adenosine residues, each mRNA molecule is theoretically able to bind a maximum of ten PABP proteins. [21] Therefore, we first tested three different molar ratios of PABP to mRNA (2:1, 10:1 and 50:1) and subsequently encapsulated them with seven different polyamines.…”
Section: Introductionmentioning
confidence: 99%